Retroperitoneal Tumors: Types and Presentations - AL•Aubaidi, Hadi M.A.; Alobaidi, Munthir; RAshed, Saad Ali (Journal of the Faculty of Medicine Baghdad, 2006)
Background :The retroperitoneal tumors is usually confined to lesions arising from tissues (muscles, fat, lymph nodes, nerves, and, developmental remnant) of this compartment but excluding origin from the retroperitoneal organs (panaceas, kidney, ureters and adrenals). The aim of the study is to focus a light on the types of retroperitoneal tumors, ways of the investigations and the presentations.Methods :A prospective review study of 25 patients with retroperitoneal tumors has been collected in the Medical City Teaching Hospitals During the period between Jan 2001 to Mar 2004. The data included age, gender, risks factors, clinical presentations, diagnostic modalities and results of histopathology. Results :14 males (56%) and 11 females (44%_ patients. The highest incidence of patients were in the (51- 60 years) age group (10/25, 40%). The most common presenting feature was abdominal mass (20/25, 80%). u/s and CT scan were the most reliable investigations in the diagnosis. The most common tumors were sarcomas (15/25, 60%) and lymphomas (5/25, 20%). Conclusion :Although retroperitoneal neoplasms account for 0.1 - 0.2% of all malignancies (s), it seems that from our findings most of the tumors were malignant, where the sarcoma represents the common tumor among them, the presentations and the diagnostic modalities especially u/s and CT have a similarity with most of the studies reviewed.